Sleep quality of maritime workers and psychosocial factors at work (Research, Society and Development, 2020)
Sleep quality is fundamental to complete well-being. Certain variables may influence the sleep-wake cycle, such as psychosocial stress related to work demands. Aim: to analyze the sleep-wake cycles of public maritime transportation workers in Rio de Janeiro and their relationship with psychosocial work stress. Methodology: this is a cross-sectional study, consisting of 312 workers. Sociodemographic, work-related, psychosocial and sleep variables were analyzed using a restricted database. Mann-Whitney and Kruskal-Wallis tests were applied and set α at 0.05. The study respected the ethical precepts of the National Health Council's resolution 466/12 and was approved by the Ethics Committee (CAAE: 55109216.4.0000.5240).  Results: significant associations were detected between high work demands and daytime sleepiness complaints, between highly demanding active work quadrants and daytime sleepiness complaints, and between high social support and daytime sleepiness complaints. High self-perceived stress was associated to sleep dissatisfaction and daytime sleepiness complaints. Conclusion: among the results found, it is noteworthy that younger workers, those who work in morning shifts and workers enrolled in study activities presented greater complaints related to the sleep-wake cycle. It is also noteworthy that working hours in the morning can be the worst work situation for maritime workers and influence the occurrence of incidents and accidents at work.